Independensi, Kompetensi Profesional dan Locus Of Control dalam Mempengaruhi Kualitas Audit Judgment - Putu Ariyati Apsari; Putu Cita ayu; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2023)
This study examines how independence, professional competence, and locus of control influence audit judgment (a case study of the Bali Province Financial Audit Board). The people in this study were the forty auditors who worked for the Audit Board of the Representatives of the Province of Bali. Forty people were chosen as samples for this study using the purposive sampling method, and the results were analyzed using multiple linear regression techniques. This study's findings demonstrate that independence positively influences audit judgment. Professional competence influences audit judgment positively; locus of control influences audit judgment positively. Based on the research results, it is hoped that in the future, the auditor will maintain a certain level of independence, use the skills they already have to form a reasonable and accurate audit opinion and learn more skills that can help them make a good audit judgment.